Heat Generation During Bone Drilling: A Comparison Between Industrial and Orthopaedic Drill Bits. Issue 2 (February 2017) - Hein, Christopher; Inceoglu, Serkan; Juma, David; Zuckerman, Lee
Abstract : Objectives: Cortical bone drilling for preparation of screw placement is common in multiple surgical fields. The heat generated while drilling may reach thresholds high enough to cause osteonecrosis. This can compromise implant stability. Orthopaedic drill bits are several orders more expensive than their similarly sized, publicly available industrial counterparts. We hypothesize that an industrial bit will generate less heat during drilling, and the bits will not generate more heat after multiple cortical passes. Methods: We compared 4 4.0 mm orthopaedic and 1 3.97 mm industrial drill bits. Three types of each bit were drilled into porcine femoral cortices 20 times. The temperature of the bone was measured with thermocouple transducers. The heat generated during the first 5 drill cycles for each bit was compared to the last 5 cycles. These data were analyzed with analysis of covariance. Results: The industrial drill bit generated the smallest mean increase in temperature (2.8 ± 0.29°C) P < 0.0001. No significant difference was identified comparing the first 5 cortices drilled to the last 5 cortices drilled for each bit. The P -values are as follows: Bosch ( P = 0.73), Emerge ( P = 0.09), Smith & Nephew ( P = 0.08), Stryker ( P = 0.086), and Synthes ( P = 0.16). The industrial bit generated less heat during drilling than its orthopaedic counterparts. The bits maintained their performance after 20 drill cycles. Conclusions: Consideration should be given by manufacturers to design differences that may contribute to a more efficient cutting bit. Further investigation into the reuse of these drill bits may be warranted, as our data suggest their efficiency is maintained after multiple uses.